Linear representations of the Lorentz group - Naimark, M. A. (Mark Aronovich) (International series in pure and applied mathematics, 1964)
The present book is devoted to a systematic exposition of the theory of linear representations of the proper Lorentz group and the complete Lorentz group. Having in mind physicist readers, the author has endeavored to make the exposition as elementary as possible, so that the reader is not expected to have any special mathematical knowledge beyond what is acquired in university courses on analysis and analytical geometry. The necessary supplementary information is given in the text itself or in the appendices.